2006
DOI: 10.1213/01.ane.0000183649.58483.77
|View full text |Cite
|
Sign up to set email alerts
|

An Iontophoretic Fentanyl Patient-Activated Analgesic Delivery System for Postoperative Pain: A Double-Blind, Placebo-Controlled Trial

Abstract: An iontophoretic fentanyl HCl patient-activated transdermal system (fentanyl HCl PATS) is under development for the treatment of acute postoperative pain. The fentanyl HCl PATS is a needle-free, credit card-sized, preprogrammed system that is applied to the patient's upper outer arm or chest. The fentanyl HCl PATS was demonstrated to be superior to placebo in a previous trial; however, the randomization scheme used and the lack of control of entry pain level may have contributed to the lack of robust findings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 17 publications
6
65
0
7
Order By: Relevance
“…Therefore, these data demonstrate that the modifications made to the original fentanyl ITS did not significantly affect the amount of fentanyl absorbed and that standard bioequivalence criteria [15] were achieved. The original fentanyl ITS was utilized in the Phase III studies that demonstrated that fentanyl ITS was superior efficacy to placebo [9,14] and has therapeutically equivalent efficacy to morphine administered i.v. as patient-controlled analgesia in adult patients with acute post-operative pain [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these data demonstrate that the modifications made to the original fentanyl ITS did not significantly affect the amount of fentanyl absorbed and that standard bioequivalence criteria [15] were achieved. The original fentanyl ITS was utilized in the Phase III studies that demonstrated that fentanyl ITS was superior efficacy to placebo [9,14] and has therapeutically equivalent efficacy to morphine administered i.v. as patient-controlled analgesia in adult patients with acute post-operative pain [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Phase III trials were performed with the original fentanyl ITS for treatment of acute postoperative pain in adult patients during hospitalization [9][10][11][12][13][14]. Patients were treated with the fentanyl ITS for up to 3 days after their operation.…”
Section: Introductionmentioning
confidence: 99%
“…A natureza não invasiva do método minimiza as complicações relacionadas à agulha e a punções venosas, além de também eliminar o risco de intervalos na analgesia, o que é inerente aos métodos não contínuos 12 . Uma preocupação importante relativa à analgesia aguda com opioides é a possibilidade de insuficiência respiratória, entretanto estudos comprovam a segurança do fentanil transdérmico para esses pacientes 6,[13][14][15] . Estudo demonstrou que o uso de fentanil por via transdérmica proporcionou analgesia satisfatória com baixas intensidades de dor.…”
Section: Discussionunclassified
“…Procedimentos cirúrgicos como artrodese de coluna são sabidamente acompanhados de grande potencial doloroso, e o fentanil transdérmico mostrou ser um grande aliado na analgesia desses pacientes. 6,17 . Algumas vantagens são a praticidade de administração do adesivo, a não dependência de acesso venoso ou de pessoal treinado em bombas de analgesia.…”
Section: Discussionunclassified
See 1 more Smart Citation